Pagans the end of traditional religion and the rise of Christianity - O'Donnell, James Joseph 1950- (New York Ecco, 2016)
Looks at the history of the rise of Christianity as experienced by the adherents of the ancient pagan religions, as they faced major disruptions brought about by the rise of what they viewed as an upstart cult
Part I. Religion without a history -- Chapter 1. The tour guide's version -- Chapter 2. The games of the century -- Chapter 3. An eloquent man who loved his country -- Chapter 4. What is a god? -- Chapter 5. Divine Butchery -- Chapter 6. Ways of knowing -- Chapter 7. The specter of atheism -- Chapter 8. Gods at home -- Chapter 9. Divine exaltation -- Part II. The history of paganism -- Chapter 10. Constantine in his world -- Chapter 11. A new leaf -- Chapter 12. The birth of paganism -- Chapter 13. The baptism of pagansim -- Chapter 14. The first Christian emperor -- Chapter 15. The servant of Christianity -- Chapter 16. The triumph of paganism -- Chapter 17. What remained -- Chapter 18. Cicero reborn -- Chapter 19. A roman religion
Includes index
Keywords: Church History -- Primitive and early church, ca. 30-600; Christianity and other religions -- Rome; Paganism -- Rome; Rome -- Religion